Prevalence of atrial fibrillation and procedural outcome in patients undergoing catheter ablation for premature ventricular complexes. (24th November 2022) - Zou, Fengwei; Di Biase, Luigi; Mohanty, Sanghamitra; Zhang, Xiaodong; Shetty, Sai Shishir; Gianni, Carola; Della Rocca, Domenico G.; Lin, Aung; Arosio, Roberto; Schiavone, Marco; Forleo, Giovanni; Mayedo, Angel; et al.
Abstract: Introduction: Atrial fibrillation (AF) and premature ventricular complexes (PVC) are common arrhythmias. We aimed to investigate AF prevalence in patients with PVC and its impact on PVC ablation outcomes. Methods: Consecutive patients undergoing PVC ablation at a single institution between 2016 and 2019 were included and prospectively followed for 2 years. Patients with severe valvular heart disease, hyperthyroidism, malignancy, alcohol use disorder and advanced renal/hepatic diseases were excluded. Twelve‐lead electrocardiograms were used to diagnose AF and assess PVC morphology. All PVCs were targeted for ablation using 4‐mm irrigated‐tip catheters at standardized radiofrequency power guided by 3‐D mapping and intracardiac echocardiography. Patients were followed with remote monitoring, device interrogations and office visits every 6 months for 2 years. Detection of any PVCs in follow‐up was considered as recurrence. Results: A total of 394 patients underwent PVC ablation and 96 (24%) had concurrent AF. Patients with PVC and AF were significantly older (68.2 ± 10.8 vs. 58.3 ± 15.8 years, p  < .001), had lower LV ejection fraction (43.3 ± 13.3% vs. 49.6 ± 12.4%, p  < .001), higher CHA2 DS2 ‐VASc (2.8 ± 1.3 vs. 2.0 ± 1.3, p  < .001) than those without. PVCs with ≥2 morphologies were detected in 60.4% and 13.7% patients with vs without AF ( p  < .001). At 2‐year follow‐up, PVC recurrence rate was significantly higher in patients with vs without AF (17.7% vs. 9.4%, p  = .02). Conclusion: AF was documented in 1/4 of patients undergoing PVC ablation and was associated with lower procedural success at long‐term follow‐up. This was likely attributed to older age, worse LV function and higher prevalence of multiple PVC morphologies in patients with concurrent AF.